2020
DOI: 10.1021/acsami.0c05732
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/CuO2 Nanoshuttles with Controllable Release of Oxygen Nanobubbles Promoting Interruption of Bacterial Respiration

Abstract: An oxygen nanoshuttle based on a reduced graphene oxide/copper peroxide (rGO/CuO 2 ) nanocomposite has been presented to deliver in situ oxygen nanobubbles (O 2 NBs) for combating bacterial infections. In the presence of rGO, the solid source of oxygen (i.e., CuO 2 ) was decomposed (in response to environmental conditions such as pH and temperature) into O 2 NBs in a more controllable and long-lasting trend (from 60 to 144 h). In a neutral buffer, the O 2 NBs experienced growth and collapse evolutions, creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(73 citation statements)
references
References 67 publications
4
69
0
Order By: Relevance
“…Notably, the viability of MCF7/Taxol cells treated with P@PTX-CuTCPP or P@PTX combined with a nontoxic dose of l -BSO was significantly lower than that of cells treated with P@PTX only, as shown in Fig. 4 C. Recent studies have demonstrated that Cu-involved nanomaterials have promising prospect in tumor theranostics [ 60 ], the antibacterial use [ 62 ] and bioimaging due to the generation of reactive oxygen species from Cu 2+ . In present study, although the low-dose use of Cu 2+ (up to 0.1 mM) alone failed to conquer tumor cells, we found that CuTCPP can be a synergist to enhance chemotherapy efficacy after encapsulaton into nanosystems.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, the viability of MCF7/Taxol cells treated with P@PTX-CuTCPP or P@PTX combined with a nontoxic dose of l -BSO was significantly lower than that of cells treated with P@PTX only, as shown in Fig. 4 C. Recent studies have demonstrated that Cu-involved nanomaterials have promising prospect in tumor theranostics [ 60 ], the antibacterial use [ 62 ] and bioimaging due to the generation of reactive oxygen species from Cu 2+ . In present study, although the low-dose use of Cu 2+ (up to 0.1 mM) alone failed to conquer tumor cells, we found that CuTCPP can be a synergist to enhance chemotherapy efficacy after encapsulaton into nanosystems.…”
Section: Resultsmentioning
confidence: 98%
“…[37] Specifically, the reaction mechanism of the proposed oriented catalytic oxidation process is illustrated in Figure 1d. When immersed in MnSO 4 aqueous solution containing H 2 O 2 , the Cu(OH) 2 nanorod template first reacts slowly with H 2 O 2 to produce CuO and low levels of O 2 (Equation І in Figure 1d and Figure S1a, Supporting Information), [38,39] in which O 2 can be exactly involved as a reactant, together with the sparse ionized OH − around the Cu(OH) 2 surfaces to directionally oxidize Mn 2+ to form Mn 3 O 4 on the nanorods (Table S1 and Figure S1b, Supporting Information, Equation ІІ in Figure 1d). [40] Immediately, such newly generated Mn 3 O 4 will serve as a catalyst to accelerate reaction І, leading to violent O 2 bubbles as well as rapid color variation of the arrays caused by the massive formation of CuO (Figures S2 and S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In another example of the multipurpose role of ONBs, the Akhavan research group devised an efficient approach for the preparation of reduced graphene oxide (rGO)/copper peroxide (CuO 2 ) nanoshuttles that also allowed the controlled release of ONBs and simultaneously inhibited bacterial respiration. 217 The oxygen carrier comprised a solid source of oxygen CuO 2 and rGO as a carrier with a photothermal-sensitizing ability, to provide the needed oxygen in situ. Subsequently, laser irradiation was used to transfer the energy into localized heat, which damaged cell membranes and increased the release rate of the ONBs.…”
Section: Multipurpose Role Of Onbs: Antimicrobial Antiinflammatory and Wound-healing Propertiesmentioning
confidence: 99%
“…The solid and dashed lines represent scale bars of 1 μm and 500 nm, respectively. Reproduced with permission from ref ( 217 ). Copyright 2020 American Chemical Society.…”
Section: Multipurpose Role Of Onbs: Antimicrobial Antiinflammatory and Wound-healing Propertiesmentioning
confidence: 99%